Zucchini Yellow Mosaic Virus Infection Limits Establishment and Severity of Powdery Mildew in Wild Populations of Cucurbita pepo - Harth, Jacquelyn E.; Ferrari, Matthew J.; Helms, Anjel M.; Tooker, John F.; Stephenson, Andrew G. (Frontiers in Plant Science, 2018)
Few studies have examined the combined effect of multiple parasites on host fitness. Previous work in the Cucurbita pepo pathosystem indicates that infection with Zucchini yellow mosaic virus (ZYMV) reduces exposure to a second insect-vectored parasite (Erwinia tracheiphila). In this study, we performed two large-scale field experiments employing wild gourds (Cucurbita pepo ssp. texana), including plants with a highly introgressed transgene conferring resistance to ZYMV, to examine the interaction of ZYMV and powdery mildew, a common fungal disease. We found that ZYMV-infected plants are more resistant to powdery mildew (i.e., less likely to experience powdery mildew infection and when infected with powdery mildew, have reduced severity of powdery mildew symptoms). As a consequence, during widespread viral epidemics, proportionally more transgenic plants get powdery mildew than non-transgenic plants, potentially mitigating the benefits of the transgene. A greenhouse study using ZYMV-inoculated and non-inoculated controls (non-transgenic plants) revealed that ZYMV-infected plants were more resistant to powdery mildew than controls, suggesting that the transgene itself had no direct effect on the powdery mildew resistance in our field study. Additionally, we found evidence of elevated levels of salicylic acid, a phytohormone that mediates anti-pathogen defenses, in ZYMV-infected plants, suggesting that viral infection induces a plant immune response (systemic acquired resistance), thereby reducing plant susceptibility to powdery mildew infection.